Effectiveness in weight gain of preterm low birth weight infants exposed to parenteral nutrition - Vargas Hernández, Jeylin (2018)
The preterm newborn (RNPT) has very high nutritional needs, which affect the weight gain after birth, which is why it starts with parenteral nutrition while it manages to adapt to enteral nutrition that benefits its growth and development even more. avoid future complications There has been sufficient discussion on the topic of parenteral nutrition, which has led health professionals to seek the best scientific evidence to support their work. The objective of this study is to analyze the best available scientific evidence regarding the effectiveness in weight gain of preterm newborns, under 37 weeks weighing less than 1500 grams, exposed to parenteral nutrition in the Neonatal Intensive Care Unit. The methodology that will be applied to develop this protocol is the clinical practice based on evidence, which consists of five steps; the clinical question, search for scientific evidence, critical analysis of the evidence, transfer of evidence and evaluation of the transfer of evidence.